Carbonate triple oxygen and carbon isotope effects of chemical pretreatments on tooth enamel and eggshell - Sarah A. Katz; Alex Bertacchi; Drake A. Yarian; Jordan A.G. Wostbrock (Chemical Geology, 2026)

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Development of a Stereolithography 3D Printing-Based Micropatterning Method to Study Endothelial-to-Mesenchymal Transition Mechanobiology - Karina Bender; Sarah Chesley; Jay Lesny Drake; Megan Ho; Emily Lin; Kathryn Saxton; Ninava Sharma; Christina K. Tripsas; Qian Li; Jeffrey J. Hsu (Annals of Biomedical Engineering, 2026)
Endothelial-to-mesenchymal transition (EndMT) is the process of endothelial cells undergoing molecular changes that shift their phenotype from that of endothelial cells to that of mesenchymal-like cells. It is a crucial developmental process that has been implicated in various physiological and pathological conditions. EndMT has gained attention as a potential therapeutic target for cardiovascular disease processes, including atherosclerosis, myocardial fibrosis, and vascular calcification. In addition to the assessment of endothelial and mesenchymal markers, the behavioral mechanics of endothelial cells, such as migration and invasion, are often used to identify endothelial cells that have undergone EndMT. However, whether cell chirality may be another mechanobiological marker of EndMT remains unclear. In this study, we aimed to develop an accessible micropatterning platform and created a stereolithography (SLA) 3D printing-based polydimethylsiloxane (PDMS) protein-stamp fabrication platform to create customized patterns of ECM proteins to study endothelial cell chirality during EndMT. Human aortic endothelial cells (HAECs) were treated with the inflammatory cytokine tumor necrosis factor-α (TNF-α), which resulted in the downregulation of the endothelial marker ENOS3 and the upregulation of the mesenchymal markers N-cadherin and transgelin, supporting the induction of EndMT. HAECs were seeded onto fibronectin stripe micropatterns, and cell chirality was measured using custom cell-profiling software. HAECs treated with TNF-α exhibited a shift in cell orientation by approximately 18°, supporting altered cell chirality during TNF-α-induced EndMT. Our work innovates novel methods of studying EndMT by developing a flexible and cost-effective protein-stamp fabrication and image analysis pipeline. This pipeline can be used by researchers to study the endothelial cell chirality in response to EndMT induction.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Trade-offs and synergies in the management of environmental pressures: a case study on ship noise mitigation - Karen de Jong; Cathryn C. Murray; Asier Anabitarte; Sarah Bailey; Lisa Drake; Jose A. Fernandes-Salvador; Ida-Maja Hassellov; Nicole Heibeck; Jukka-Pekka Jalkanen; Annukka Lehikoinen; Nathan Merchant; Amanda T. Nylund; et al. (Marine Pollution Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Friend or foe? The role of biotic agents in drought-induced plant mortality - Robert J. Griffin-Nolan; Neha Mohanbabu; Sarah Araldi-Brondolo; Alexander R. Ebert; Julie LeVonne; Joanna I. Lumbsden-Pinto; Hannah Roden; Jordan R. Stark; Jordon Tourville; Katie M. Becklin; John E. Drake; Douglas A. Frank; et al. (Plant Ecology, 2021)

Contrasting latitudinal gradients of body size in helminth parasites and their hosts - Tad Dallas; Alyssa‐Lois M. Gehman; A. Alonso Aguirre; Sarah A. Budischak; John M. Drake; Maxwell J. Farrell; Ria Ghai; Shan Huang; Ignacio Morales‐Castilla (Global Ecology and Biogeography, 2019)
Aim We examined body size scaling relationships for two developmental life stages of parasitic helminths (egg and adult) separately in relationship to latitude (i.e. Bergmann's rule), temperature and temperature seasonality. Given that helminth eggs experience environmental conditions more directly, whereas adults live inside infected host individuals, we predict stronger environmentally driven gradients of body size for eggs than for adults. Location Global. Time period Present day. Major taxa studied Parasitic helminths. Methods We compiled egg size and adult body size data (both minimum and maximum) for 265 parasitic helminth species from the literature, along with species latitudinal distribution information using an extensive global helminth occurrence database. We then examined how the average helminth egg and adult body size of all helminth species present (minimum and maximum separately) scaled with latitude, temperature and temperature variability, using generalized linear models. Results Both the egg size and the adult body size of helminths tended to decrease towards higher latitudes, although we found the opposite body size scaling pattern for their host species. Helminth sizes were also positively correlated with temperature and negatively, but more weakly, with temperature seasonality. Main conclusions Instead of following the body size patterns of their hosts, helminth parasites are more similar to other ectotherms in that they follow the converse Bergmann's rule. This pattern did not differ between helminth developmental stages, suggesting that mean annual temperature and seasonality are unlikely to be related mechanistically to body size variation in this case.

Development of Plain Language Supplemental Materials for the Biobank Informed Consent Process - Bettina F. Drake; Katherine M. Brown; Sarah Gehlert; Leslie E. Wolf; Joann Seo; Hannah Perkins; Melody S. Goodman; Kimberly A. Kaphingst (Journal of Cancer Education, 2017)

Barriers and Strategies to Participation in Tissue Research Among African-American Men - Bettina F. Drake; Danielle Boyd; Kimberly Carter; Sarah Gehlert; Vetta Sanders Thompson (Journal of Cancer Education, 2017)

The marine cytotoxin portimine is a potent and selective inducer of apoptosis - Sarah L. Cuddihy; Sarah Drake; D. Tim Harwood; Andrew I. Selwood; Paul S. McNabb; Mark B. Hampton (Apoptosis, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Differences in preferences for models of consent for biobanks between Black and White women - Katherine M. Brown; Bettina F. Drake; Sarah Gehlert; Leslie E. Wolf; James DuBois; Joann Seo; Krista Woodward; Hannah Perkins; Melody S. Goodman; Kimberly A. Kaphingst (Journal of Community Genetics, 2016)

Variation in propagule and colonization pressures following rapid human‐mediated transport: Implications for a universal assemblage‐based management model - Elizabeta Briski; D. Andrew R. Drake; Farrah T. Chan; Sarah A. Bailey; Hugh J. MacIsaac (Limnology and Oceanography, 2014)
Recent studies have recognized the importance of propagule pressure (number of individuals) and colonization pressure (number of species) for explaining establishment success of nonindigenous species. However, the International Ballast Water Management Convention, when ratified, will require ships to satisfy a numeric discharge standard that focuses only on cumulative propagule pressure of all individuals released. Because of practical constraints, the standard does not differentiate between discharges of single vs. multiple species. The assemblage‐based approach, which uses rank‐abundance gradients to quantify and manage introduction risk, may compensate for this limitation (e.g., even gradient [relatively consistent propagule pressures among n transported species] or uneven gradient [uneven propagule pressures among n transported species]). Here we explore species abundance distributions of zooplankton during transportation in ballast water to assess variability in the structure of assemblages, with implications for the potential development of an assemblage‐based management model. Specifically, we explored species abundance distributions for voyages that lasted

Invasion in space and time: non‐native species richness and relative abundance respond to interannual variation in productivity and diversity - Elsa E. Cleland; Melinda D. Smith; Sandy J. Andelman; Christy Bowles; Karen M. Carney; M. Claire Horner‐Devine; John M. Drake; Sarah M. Emery; Joel M. Gramling; David B. Vandermast (Ecology Letters, 2004)
Ecologists have long sought to understand the relationships among species diversity, community productivity and invasion by non‐native species. Here, four long‐term observational datasets were analyzed using repeated measures statistics to determine how plant species richness and community resource capture (i.e. productivity) influenced invasion. Multiple factors influenced the results, including the metric used to quantify invasion, interannual variation and spatial scale. Native richness was positively correlated with non‐native richness, but was usually negatively correlated with non‐native abundance, and these patterns were stronger at the larger spatial scale. Logistic regressions indicated that the probability of invasion was reduced both within and following years with high productivity, except at the desert grassland site where high productivity was associated with increased invasion. Our analysis suggests that while non‐natives were most likely to establish in species rich communities, their success was diminished by high resource capture by the resident community.